ENTREPRENEURIAL COMPETENCIES FOR DETERMINING BUSINESS SUCCESS IN INDONESIA - Yuldinawati, Lia; Yelliantty, Yelliantty (Faculty of Economic and Business, University of Pasundan, 2024)
Entrepreneurship plays a crucial role in developing countries by creating employment opportunities and reducing unemployment. This study addresses those issues by examining the impact of entrepreneurial competencies on business success. The novelty relies on its empirical study which is still lacking among Indonesian literature concerning entrepreneurial competencies. This study used PLS-SEM to investigate eight dimensions of entrepreneurial competencies: learning, ethical, familism, relationship, conceptual, opportunity, personal, and strategic competencies. The findings revealed a positive and substantial impact of entrepreneurial competencies on business success. All dimensions are equally important, underscoring the need for stakeholders to prioritize the development of these competencies among young entrepreneurs for the sustainability and growth of their businesses. This study can be a valuable reference and insight for other researchers and Indonesian government to improve business performance among young entrepreneurs.